Environmental DNA-based assessment of multitrophic biodiversity in a typical river located in the Loess Plateau, China: Influence of PAHs and suspended sediments - Qian Li; Yulu Tian; Yongrong Hao; Chengkai Qu; Rungnapa Tagun; Hisato Iwata; Jiahua Guo (Ecotoxicology and Environmental Safety)
Polycyclic aromatic hydrocarbon (PAH) pollution and high suspended sediment (SS) contents are significant anthropogenic and natural stressors that threaten aquatic biodiversity. However, the characteristics of multitrophic biological communities and their co-occurrence patterns in response to PAHs in sediment-laden rivers remain unclear. This study investigated the spatial distribution of species across three trophic levels, including algae, metazoan, and fish, in the Beiluo River on the Loess Plateau, China, using environmental DNA metabarcoding. Biodiversity was assessed in relation to 16 PAHs, SS, and environmental variables. The PAH in the dissolved phase ranged from 19.70 to 1613.30 ng/L dominated by low molecular weight (LMW) PAHs. Partial least squares path modeling (PLS-PM) revealed a negative correlation between PAH distribution and SS in the river. In terms of biodiversity, the richness and Shannon index of algae (Chlorophyta and Dinophyceae) were positively associated with acenaphthene (ACE) levels. Conversely, the Shannon index and richness of metazoans (Rotifera and Arthropoda) appeared to decline in response to Benzo[a]anthracene (BaA) and pyrene (PYR). Fishes (Cypriniformes and Clupeiformes) demonstrated greater tolerance to PAH contamination than algae and metazoans, and their reduced richness and Shannon index were linked to the high SS loads (> 0.45 μm). The co-occurrence patterns highlighted a stronger association connection between algae and metazoan communities than fish. This study provides valuable insights into how PAHs could reshape the structure of riverine multitrophic communities under conditions of elevated SS loads.